2021
DOI: 10.3390/antibiotics10111389
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sociodemographic Factors, Parity and Cervical Cancer on Antibiotic Treatment for Uncomplicated Cystitis in Women: A Nationwide Cohort Study

Abstract: Background: Uncomplicated cystitis is one of the most common reasons for antibiotic treatment in otherwise healthy women. Nationwide studies on antibiotic treatment for this infection and in relation to factors beyond the infection itself have hitherto not been available. Methods: This was a nationwide open cohort study consisting of 352,507 women aged 15–50 years with uncomplicated cystitis (2006–2018). The outcome was a redeemed antibiotic prescription within five days from the cystitis diagnosis. Logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 28 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…For country of origin, only MENA women had lower odds of fluoroquinolone compared to Swedish-born women (although statistically non-significant), while women from Asia (excluding Middle East) and Oceania, Western countries, and Latin America and the Caribbean had weak but significantly higher odds of fluoroquinolone treatment compared to Swedish-born women. The mechanisms behind these sociodemographic differences in fluoroquinolone treatment of uncomplicated cystitis, which were similar to the odds for antibiotic treatment in general [ 4 ], could, inter alia, be attributed to uncertainty in diagnostic testing [ 18 ]. During the last decade, it has not been recommended to prescribe fluoroquinolones as a first-line prescription for uncomplicated cystitis [ 19 ], as these antibiotics ought to be limited to serious infections and not uncomplicated cystitis due to concern of worrisome collateral damage and adverse effects associated with these antibiotics [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For country of origin, only MENA women had lower odds of fluoroquinolone compared to Swedish-born women (although statistically non-significant), while women from Asia (excluding Middle East) and Oceania, Western countries, and Latin America and the Caribbean had weak but significantly higher odds of fluoroquinolone treatment compared to Swedish-born women. The mechanisms behind these sociodemographic differences in fluoroquinolone treatment of uncomplicated cystitis, which were similar to the odds for antibiotic treatment in general [ 4 ], could, inter alia, be attributed to uncertainty in diagnostic testing [ 18 ]. During the last decade, it has not been recommended to prescribe fluoroquinolones as a first-line prescription for uncomplicated cystitis [ 19 ], as these antibiotics ought to be limited to serious infections and not uncomplicated cystitis due to concern of worrisome collateral damage and adverse effects associated with these antibiotics [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, no firm conclusion can be made on whether the differences in fluoroquinolone treatment could have been due to unequal healthcare (differences in prescription rates) or differences in adherence (differences in pick-up rates). Further studies could examine possible mechanisms behind the found associations of factors likely beyond the infection and antibiotic treatments [ 4 ]. The main strengths of this study include that this study involved several highly validated nationwide patient and population data registries including nationwide primary healthcare data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations